Pellet manufacturing method, pellet and ion exchange membrane

The method of producing pellets from fluoropolymers with specific ion exchange capacity and controlled extrusion temperature, combined with surface roughening, addresses voltage fluctuations in ion exchange membranes, ensuring stable electrolysis performance.

JP7601136B2Active Publication Date: 2024-12-17AGC INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023070829
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-09-14
Filing Date
2023-04-24
Publication Date
2024-12-17
Estimated Expiration
2039-09-11

AI Technical Summary

Technical Problem

Ion exchange membranes using fluorine-containing polymers exhibit wide fluctuations in electrolysis voltage, affecting production efficiency.

Method used

A method for producing pellets from fluoropolymers with an ion exchange capacity of 1.1 meq/g resin or more, extruded at a die temperature below 200°C, and surface roughening to prevent sticking, resulting in uniform film thickness and stable electrolysis voltage.

Benefits of technology

Suppresses pressure fluctuations during film forming, achieving an ion exchange membrane with excellent electrolysis voltage stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601136000010
    Figure 0007601136000010
  • Figure 0007601136000001
    Figure 0007601136000001
  • Figure 0007601136000002
    Figure 0007601136000002
Patent Text Reader

Abstract

To provide a method for producing a pellet which enables formation of an ion exchange membrane that is excellent in stability of an electrolytic voltage, a pellet, and an ion exchange membrane.SOLUTION: A method for producing a pellet includes extruding a molten material containing a fluorine-containing polymer having a group convertible to an ion exchange group from a die of a melt extruder, obtaining a strand containing the fluorine-containing polymer, and then cutting the strand and obtaining a pellet containing the fluorine-containing polymer, wherein a temperature of the die when the molten material containing the fluorine-containing polymer is extruded from the die is lower than 200°C, and an ion exchange capacity of the fluorine-containing polymer when the group convertible to the ion exchange group of the fluorine-containing polymer is exchanged to the ion exchange group is 1.1 meq / g resin or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing pellets, a pellet, and an ion exchange membrane. [Background technology]

[0002] 2. Description of the Related Art Ion exchange membranes containing fluorine-containing polymers having ion exchange groups are used in various batteries, electrolysis processes, and processes for separating ions and the like. As a method for producing an ion exchange membrane containing a fluoropolymer, a method is known in which pellets of a fluoropolymer having an ion exchange group or a group that can be converted to an ion exchange group are used as a raw material (see Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2013 / 115072 Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, from the viewpoint of production efficiency, electrolysis devices including ion exchange membranes are required to have excellent stability of electrolysis voltage (small fluctuation range of electrolysis voltage). When the present inventors applied an ion exchange membrane obtained using pellets of the fluoropolymer described in Patent Document 1 to an electrolysis device, they found that the fluctuation range of the electrolysis voltage was large and there was room for improvement.

[0005] In view of the above problems, an object of the present invention is to provide a method for producing pellets that can provide an ion exchange membrane having excellent electrolysis voltage stability, and to provide the pellets and the ion exchange membrane. [Means for solving the problem]

[0006] As a result of intensive research by the present inventors to achieve the above-mentioned object, they have found that when pellets containing a fluoropolymer are produced using a fluoropolymer having groups convertible to ion exchange groups, the ion exchange capacity when the groups convertible to ion exchange groups are converted to ion exchange groups is 1.1 milliequivalents / gram dry resin (hereinafter also referred to as meq / g resin) or more, and the die temperature when the molten fluoropolymer is extruded through the die of a melt kneader is set to less than 200°C, thereby achieving the present invention.

[0007] The present invention has the following aspects. [1] A method for producing pellets, comprising extruding a melt containing a fluoropolymer having a group convertible to an ion-exchange group through a die of a melt extruder to obtain strands containing the fluoropolymer, and then cutting the strands to obtain pellets containing the fluoropolymer, comprising the steps of: the temperature of the die when the melt containing the fluoropolymer is extruded from the die is less than 200° C., A method for producing pellets, characterized in that when the groups convertible to ion-exchange groups of the above fluoropolymer are converted into ion-exchange groups, the ion-exchange capacity of the fluoropolymer is 1.1 meq / g resin or more. [2] The production method according to the above [1], which comprises cutting the strands to obtain pellets containing a fluoropolymer having a light transmittance of 30 to 60%. [3] The method according to [1] or [2] above, wherein the ion exchange capacity of the fluoropolymer obtained when the groups convertible to ion exchange groups of the fluoropolymer are converted to ion exchange groups is not more than 2.00 milliequivalents / gram of dry resin. [4] The method according to any one of the above [1] to [3], wherein the group that can be converted into an ion-exchange group is a group that can be converted into a carboxylic acid type functional group or a group that can be converted into a sulfonic acid type functional group. [5] The process according to any one of the above [1] to [4], wherein the fluoropolymer having a group convertible to an ion-exchange group is a copolymer of a fluoroolefin and a monomer represented by the following formula (1): Formula (1): CF2 = CF-(O)p -(CF2) q -(CF2CFX) r -(O) s -(CF2) t -(CF2CFX') u -A 1 (X and X' are each independently a fluorine atom or a trifluoromethyl group. 1 is a group that can be converted into a carboxylic acid type functional group. p is an integer of 0 or 1. q is an integer of 0 to 12. r is an integer of 0 to 3. s is an integer of 0 or 1. t is an integer of 0 to 12. u is an integer of 0 to 3, provided that 1≦p+s and 1≦r+u are satisfied. [6] The process according to any one of the above [1] to [4], wherein the fluoropolymer having a group convertible to an ion-exchange group is a copolymer of a fluorine-containing olefin and a monomer represented by the following formula (2): Formula (2): CF2 = CF-L - (A) n (L is an (n+1)-valent perfluorohydrocarbon group which may contain an oxygen atom. n is 1 or 2. A is a group which can be converted into a sulfonic acid type functional group.) [7] The method according to [6] above, wherein the monomer represented by formula (2) is a compound represented by formula (2-1), a compound represented by formula (2-2), or a compound represented by formula (2-3). Formula (2-1): CF2 = CF-OR f1 -A Formula (2-2): CF2 = CF-R f1 -A [ka] (R f1 R is a perfluoroalkylene group which may contain an oxygen atom between carbon atoms. f2 is a single bond or a perfluoroalkylene group which may contain an oxygen atom between carbon atoms. A is as defined in formula 2(B).)[8] The method according to any one of the above [1] to [7] for use in producing an ion exchange membrane. [9] A fluorine-containing polymer having a group that can be converted into an ion-exchange group, the ion exchange capacity of the fluoropolymer when the groups convertible to ion exchange groups of the fluoropolymer are converted to ion exchange groups is 1.1 meq / g resin or more; A pellet characterized by having a light transmittance of 30 to 60%.

[10] The pellet according to the above [9], wherein the group that can be converted into an ion exchange group is a group that can be converted into a carboxylic acid type functional group or a group that can be converted into a sulfonic acid type functional group.

[11] Pellets according to the above [9] or

[10] for use in the production of an ion exchange membrane.

[12] An ion exchange membrane formed using any one of the pellets [9] to

[11] above.

[13] The ion exchange membrane of

[13] above, having a membrane thickness of 30 to 180 μm.

[14] The ion exchange membrane according to

[12] or

[13] above, used for the electrolysis of an aqueous alkali chloride solution. Effect of the Invention

[0008] According to the present invention, pressure fluctuation during film molding to form an ion exchange membrane is suppressed, and an ion exchange membrane with excellent uniformity in thickness can be obtained. As a result, when applied to an electrolysis device, variations in electrolysis voltage can be suppressed, and an ion exchange membrane with excellent stability in electrolysis voltage can be formed. A pellet manufacturing method, pellets, and ion exchange membrane are provided. [Brief description of the drawings]

[0009] [Figure 1] 1 shows a photograph (magnification: 30 times) of the appearance of the pellets obtained in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The terms used in the present invention have the following meanings. The term "ion exchange group" refers to a group capable of exchanging at least a portion of the ions contained in this group for other ions, and examples thereof include the following sulfonic acid type functional groups and carboxylic acid type functional groups. "Sulfonic acid functional group" refers to a sulfonic acid group (-SO3H) or a sulfonate group (-SO3M 2 However, M 2 is an alkali metal or quaternary ammonium cation. "Carboxylic acid functional group" refers to a carboxylic acid group (-COOH) or a carboxylate group (-COOM 1 However, M 1 is an alkali metal or quaternary ammonium cation. A "precursor membrane" is a membrane that includes a polymer having groups that can be converted to ion-exchange groups. The term "group that can be converted into an ion-exchange group" refers to a group that can be converted into an ion-exchange group by hydrolysis, acidification, salt exchange with a metal cation, or other treatment. The term "group that can be converted into a sulfonic acid functional group" refers to a group that can be converted into a sulfonic acid functional group by treatment such as hydrolysis or conversion to an acid form. The term "group that can be converted into a carboxylic acid functional group" refers to a group that can be converted into a carboxylic acid functional group by a known treatment such as hydrolysis or acidification. The term "perfluorohydrocarbon group" refers to a hydrocarbon group in which all of the hydrogen atoms have been replaced with fluorine atoms. The term "perfluoroaliphatic hydrocarbon group" means an aliphatic hydrocarbon group in which all of the hydrogen atoms have been replaced with fluorine atoms.

[0011] The term "unit" in a polymer refers to an atomic group formed by polymerization of a monomer and derived from one molecule of the monomer. The unit may be an atomic group formed directly by a polymerization reaction, or may be an atomic group in which a part of the atomic group is converted into a different structure by treating the polymer obtained by the polymerization reaction.

[0012] The term "reinforcing material" refers to a material used to improve the strength of the ion exchange membrane. As the reinforcing material, a material derived from a reinforcing cloth is preferable. "Reinforcing fabric" refers to a fabric used as a raw material for a reinforcing material for improving the strength of an ion exchange membrane. The "reinforcing thread" is a thread that constitutes the reinforcing cloth and is a thread that does not dissolve in the operating environment of the device containing the ion exchange membrane. The "reinforcing thread" is preferably a thread made of a material that does not dissolve even when the reinforcing cloth is immersed in an alkaline aqueous solution (for example, a sodium hydroxide aqueous solution with a concentration of 32% by mass). The "sacrificial yarn" is a yarn that constitutes the reinforcing fabric and is at least partially dissolved in the operating environment of the device including the ion exchange membrane. The "sacrificial yarn" is preferably a yarn made of a material that dissolves in an alkaline aqueous solution when the reinforcing fabric is immersed in the alkaline aqueous solution. A numerical range expressed using "~" means a range that includes the numerical values ​​before and after "~" as the lower and upper limits. In addition, if the units of the lower and upper limits are the same, the unit of the lower limit may be omitted.

[0013] [Pellet manufacturing method] The method for producing pellets of the present invention (hereinafter also referred to as the present production method) is a method for producing pellets, comprising extruding a melt containing a fluoropolymer having a group convertible to an ion-exchange group (hereinafter also referred to as the fluoropolymer (I')) through a die of a melt extruder to obtain a strand containing the fluoropolymer (I'), and then cutting the strand to obtain pellets containing the fluoropolymer (I'). In the present production method, the temperature of the die when the melt containing the fluoropolymer (I') is extruded from the die is lower than 200°C. In the present production method, the ion exchange capacity of the fluoropolymer (hereinafter also referred to as fluoropolymer (I)) when the groups convertible to ion exchange groups of the fluoropolymer (I') are converted to ion exchange groups is 1.1 meq / g resin or more.

[0014] According to the present production method, it is possible to obtain pellets capable of forming an ion exchange membrane having excellent stability against electrolysis voltage. Although the details of the reason for this are not clear, it is presumed to be due to the following reasons. One of the causes of the variation in electrolysis voltage is the non-uniformity of the thickness of the ion exchange membrane. It is considered that such non-uniformity of the thickness of the ion exchange membrane occurs when pellets containing the fluoropolymer (I') are used to produce a film-like ion exchange membrane, because the pellets stick to each other, causing large pressure fluctuations during film formation. In addition, the sticking of pellets becomes prominent when a fluoropolymer is used as the raw material, which can become a fluoropolymer with high ion exchange capacity when a group that can be converted into an ion exchange group is converted into an ion exchange group.

[0015] To solve this problem, it was found that if the die temperature when the melt containing the fluoropolymer (I') is extruded from the die is lowered, the surface of the strands (pellets) is roughened by the occurrence of melt fracture (specifically, multiple grooves are formed on the pellet surface), and adhesion between the pellets can be suppressed. This suppresses pressure fluctuations during film molding, and an ion exchange membrane with excellent uniformity in film thickness is obtained, which is thought to suppress variations in electrolysis voltage when the ion exchange membrane is applied to an electrolysis device.

[0016] An example of this manufacturing method will be described below. First, a fluoropolymer having a group that can be converted into an ion-exchange group is fed into a melt extruder to obtain a melt of the fluoropolymer. The melt extruder may be a known device, and specific examples thereof include a single screw extruder, a twin screw extruder, and a tandem extruder. The melting temperature of the fluoropolymer (I') is preferably from 150 to 350°C, particularly preferably from 200 to 300°C.

[0017] Next, the melt of the fluoropolymer (I') is extruded from a die at the tip of the melt extruder and cooled to obtain a strand containing the fluoropolymer (I'), which is then cut into a predetermined size to obtain pellets containing the fluoropolymer (I'). In the present example of the production method, the so-called strand cut method is used as the pellet cutting method, but an underwater cut method, a hot cut method, or the like may also be used.

[0018] Here, the temperature of the die when the melt containing the fluoropolymer (I') is extruded through the die (hereinafter also simply referred to as the die temperature) is less than 200°C, and from the viewpoint of better stability of the electrolysis voltage, it is preferably 190°C or less, more preferably 170°C or less, particularly preferably 150°C or less, and most preferably 145°C or less. The die temperature is preferably 140° C. or higher, more preferably 142° C. or higher, since this facilitates extrusion of the melt of the fluoropolymer (I') from the die. In particular, when the ion exchange capacity of the fluoropolymer (i.e., the fluoropolymer (I)) when groups convertible to ion exchange groups of the fluoropolymer (I') are converted to ion exchange groups is 1.2 meq / g resin or more, the die temperature is preferably 140°C or more and less than 200°C, more preferably 140 to 150°C, particularly preferably 140 to 145°C, from the viewpoints of better stability of the electrolysis voltage and better electrolysis efficiency.

[0019] The shape of the pellets obtained by the present production method is not particularly limited, and may be, for example, any shape such as a sphere (including an ellipsoid) or a columnar shape (for example, a cylindrical shape). The size of the pellets obtained by this production method is not particularly limited, but for example, when the pellets are cylindrical, they preferably have a diameter of 2 to 3 mm and a length of 2 to 3 mm.

[0020] The surface of the pellets (strands) obtained by this production method preferably has a plurality of grooves formed thereon, which makes it possible to prevent the pellets from sticking together. The grooves formed on the surface of the pellet may be formed over the entire surface of the pellet, but usually it is preferred that they are formed only on the side surface of the pellet (surfaces other than the cut surfaces of the strands). The grooves formed on the surface of the pellet are preferably formed mainly along a direction intersecting the cut surface of the pellet (the flow direction of the strand).

[0021] In the present production method, after cutting the strands, a roughening treatment may be carried out to roughen the surfaces of the pellets, which makes the surfaces of the pellets more rough and more effectively prevents the pellets from sticking to each other, thereby providing an ion exchange membrane with better stability in the electrolysis voltage. A specific example of the surface roughening treatment method is a method in which pellets are stirred using a mixer (eg, a V blender).

[0022] The pellets obtained by this production method are preferably used for producing ion exchange membranes, specific examples of uses of the ion exchange membranes will be described later.

[0023] [Fluorine-containing polymer (I')] The fluoropolymer (I') used in the present production method is a fluoropolymer having a group that can be converted into an ion-exchange group. The group that can be converted into an ion-exchange group is preferably a group that can be converted into a carboxylic acid type functional group or a group that can be converted into a sulfonic acid type functional group.

[0024] The ion exchange capacity of the fluoropolymer (i.e., fluoropolymer (I)) when groups convertible to ion exchange groups of the fluoropolymer (I') are converted to ion exchange groups is 1.1 meq / g resin or more, and from the viewpoint of enabling a reduction in the electrolysis voltage of the apparatus, it is particularly preferably 1.20 meq / g resin or more, and from the viewpoint of better strength of the ion exchange membrane, it is preferably 2.00 meq / g resin or less, and particularly preferably 1.90 meq / g resin or less. Here, the fluoropolymer (I) for measuring the ion exchange capacity is obtained as follows. First, the fluoropolymer (I') that has been vacuum heat-treated at 240°C and -0.1 MPaG for 16 hours is immersed in a solution of dimethylsulfoxide / potassium hydroxide / water = 30 / 5.5 / 64.5 (mass ratio) at 95°C for 30 minutes to hydrolyze groups that can be converted into ion exchange groups in the fluoropolymer (I') and convert them into K-type ion exchange groups, and then washed with water. Thereafter, the polymer is immersed in an aqueous sodium hydroxide solution to convert the terminal groups from K-type to Na-type, thereby obtaining the fluoropolymer (I) for measuring the ion exchange capacity. The ion exchange capacity of the thus obtained fluoropolymer (I) can be measured by a method as described later in the Examples section.

[0025] The fluoropolymer (I') may be used either alone or in combination of two or more kinds. The fluoropolymer (I') is preferably a fluoropolymer having a group which can be converted into a carboxylic acid type functional group (hereinafter also referred to as a fluoropolymer (C')), or a fluoropolymer having a group which can be converted into a sulfonic acid type functional group (hereinafter also referred to as a fluoropolymer (S')), in terms of enabling the effects of the present invention to be more effectively exhibited. Each of the fluoropolymers will be described in detail below.

[0026] (Fluorine-containing polymer (C')) The fluorine-containing polymer (C') is more preferably a copolymer of a fluorine-containing olefin and a monomer having a fluorine atom and a group that can be converted into a carboxylic acid type functional group (hereinafter also referred to as fluorine-containing monomer (C')), since this allows the effects of the present invention to be more effectively exhibited. The copolymerization method may be a known method such as solution polymerization, suspension polymerization, or emulsion polymerization.

[0027] The fluorine-containing monomer (C') is not particularly limited as long as it is a compound having one or more fluorine atoms in the molecule, an ethylenic double bond, and a group that can be converted into a carboxylic acid functional group, and any conventionally known compound can be used. The fluorine-containing monomer (C') is preferably a monomer represented by the following formula (1) from the viewpoints of the production cost of the monomer, the reactivity with other monomers, and excellent properties of the resulting fluorine-containing polymer.

[0028] Formula (1): CF2=CF-(O) p -(CF2) q -(CF2CFX) r -(O) s -(CF2) t -(CF2CFX') u -A 1

[0029] In formula (1), X and X' are each independently a fluorine atom or a trifluoromethyl group. 1 is a group that can be converted to a carboxylic acid type functional group. Specifically, -CN, -COF, -COOR 1 (R 1 is an alkyl group having 1 to 10 carbon atoms, -COONR 2 R 3 (R 2 and R 3 are each independently a hydrogen atom or an alkyl group having 1 to 10 carbon atoms. p is an integer of 0 or 1. q is an integer of 0 to 12. r is an integer of 0 to 3. s is an integer of 0 or 1. t is an integer of 0 to 12. u is an integer of 0 to 3, with the proviso that 1≦p+s and 1≦r+u are satisfied.

[0030] Specific examples of the monomer represented by formula (1) include the following compounds, and from the viewpoint of ease of production, a compound in which p=1, q=0, r=1, s=0-1, t=0-3, and u=0-1 is preferred. CF2=CF-O-CF2CF2-COOCH3, CF2=CF-O-CF2CF2CF2-COOCH3, CF2=CF-O-CF2CF2CF2CF2-COOCH3, CF2=CF-O-CF2CF2-O-CF2CF2-COOCH3, CF2=CF-O-CF2CF2-O-CF2CF2CF2-COOCH3, CF2=CF-O-CF2CF2-O-CF2CF2CF2CF2-COOCH3, CF2=CF-O-CF2CF2CF2-O-CF2CF2-COOCH3, CF2=CF-O-CF2CF(CF3)-O-CF2CF2-COOCH3, CF2=CF-O-CF2CF(CF3)-O-CF2CF2CF2-COOCH3. The fluorine-containing monomer (C') may be used alone or in combination of two or more kinds.

[0031] The fluorine-containing olefin may be a fluoroolefin having 2 to 3 carbon atoms and having one or more fluorine atoms in the molecule. Specific examples thereof include tetrafluoroethylene (TFE), chlorotrifluoroethylene, vinylidene fluoride, vinyl fluoride, and hexafluoropropylene. Among these, TFE is particularly preferred in terms of the production cost of the monomer, reactivity with other monomers, and excellent properties of the resulting fluorine-containing polymer. The fluorine-containing olefins may be used alone or in combination of two or more kinds.

[0032] In the production of the fluoropolymer (C'), in addition to the fluoromonomer (C') and the fluoroolefin, other monomers may be used. Specific examples of other monomers include CF2=CFR f (R f is a perfluoroalkyl group having 2 to 10 carbon atoms, CF2=CF-OR f1 (R f1 is a perfluoroalkyl group having 1 to 10 carbon atoms.) CF2=CFO(CF2) v CF=CF2 (wherein v is an integer of 1 to 3). By copolymerizing other monomers, the flexibility and mechanical strength of the ion exchange membrane can be improved. The content of units based on other monomers is preferably not more than 30 mass % based on all units in the fluoropolymer (C') from the viewpoint of maintaining the ion exchange performance.

[0033] (Fluorine-containing polymer (S')) The fluorine-containing polymer (S') is more preferably a copolymer of a fluorine-containing olefin and a monomer having a fluorine atom and a group that can be converted into a sulfonic acid functional group (hereinafter also referred to as a fluorine-containing monomer (S')), since this allows the effects of the present invention to be more effectively exhibited. The copolymerization method may be a known method such as solution polymerization, suspension polymerization, or emulsion polymerization.

[0034] The fluorine-containing olefin may be any of those exemplified above, with TFE being preferred from the viewpoints of monomer production cost, reactivity with other monomers, and excellent properties of the resulting fluorine-containing polymer (S'). The fluorine-containing olefins may be used alone or in combination of two or more kinds.

[0035] The fluorine-containing monomer (S') may be a compound having one or more fluorine atoms in the molecule, an ethylenic double bond, and a group that can be converted into a sulfonic acid type functional group. As the fluorine-containing monomer (S'), a compound represented by formula (2) is preferred from the viewpoints of the production cost of the monomer, the reactivity with other monomers, and excellent properties of the resulting fluorine-containing polymer (S'). Equation (2) CF2 = CF-L-(A) n

[0036] L is an (n+1) valent perfluorohydrocarbon group which may contain an oxygen atom. The oxygen atom may be located at a terminal position in the perfluorohydrocarbon group or between carbon atoms. The (n+1) valent perfluorohydrocarbon group preferably has 1 or more carbon atoms, more preferably 2 or more carbon atoms, and preferably has 20 or less carbon atoms, more preferably 10 or less carbon atoms.

[0037] L is preferably a n+1 valent perfluoroaliphatic hydrocarbon group which may contain an oxygen atom, more preferably a divalent perfluoroalkylene group which may contain an oxygen atom in the embodiment of n = 1, or a trivalent perfluoroaliphatic hydrocarbon group which may contain an oxygen atom in the embodiment of n = 2. The divalent perfluoroalkylene group may be either linear or branched.

[0038] n is an integer of 1 or 2. A is a group that can be converted into a sulfonic acid functional group. The group that can be converted into a sulfonic acid functional group is preferably a functional group that can be converted into a sulfonic acid functional group by hydrolysis. Specific examples of groups that can be converted into a sulfonic acid functional group include -SO2F, -SO2Cl, and -SO2Br.

[0039] The compound represented by formula (2) is preferably a compound represented by formula (2-1), a compound represented by formula (2-2), or a compound represented by formula (2-3). Equation (2-1): CF2=CF-OR f1 -A Equation (2-2): CF2 = CF-R f1 -A

[0040] [ka]

[0041] R f1 is a perfluoroalkylene group which may contain an oxygen atom between carbon atoms. The number of carbon atoms in the perfluoroalkylene group is preferably 1 or more, more preferably 2 or more, and is preferably 20 or less, more preferably 10 or less. R f2 is a perfluoroalkylene group which may contain a single bond or an oxygen atom between carbon atoms. The number of carbon atoms in the perfluoroalkylene group is preferably 1 or more, more preferably 2 or more, and is preferably 20 or less, more preferably 10 or less. r is 0 or 1. R in the formulaf2 is a single bond or a perfluoroalkylene group which may contain an oxygen atom between carbon atoms. In the formula, A is defined as above.

[0042] Specific examples of the compound represented by formula (2-1) include the following compounds: In the formula, w is an integer of 1 to 8, and x is an integer of 1 to 5. CF2=CF-O-(CF2) w -SO2F CF2 = CF-O-CF2CF(CF3)-O-(CF2) w -SO2F CF2=CF-[O-CF2CF(CF3)] x -SO2F

[0043] Specific examples of the compound represented by formula (2-2) include the following compounds: In the formula, w is an integer of 1 to 8. CF2=CF-(CF2) w -SO2F CF2=CF-CF2-O-(CF2) w -SO2F

[0044] The compound represented by formula (2-3) is preferably a compound represented by formula (2-3-1). f3 is a linear perfluoroalkylene group having 1 to 6 carbon atoms, and R f4 represents a single bond or a linear perfluoroalkylene group having 1 to 6 carbon atoms which may contain an oxygen atom between carbon atoms. The definitions of r and A in the formula are as described above.

[0045] [ka]

[0046] Specific examples of the compound represented by formula (2-3-1) include the following.

[0047] [ka]

[0048] The fluorine-containing monomer (S') may be used alone or in combination of two or more kinds. In the production of the fluoropolymer (S'), in addition to the fluorine-containing olefin and the fluorine-containing monomer (S'), other monomers may be used. Examples of the other monomers include those exemplified above. The content of units based on other monomers is preferably at most 30 mass % based on all units in the fluoropolymer (S') from the viewpoint of maintaining the ion exchange performance.

[0049] [pellet] The pellets of the present invention (hereinafter also referred to as the present pellets) contain a fluoropolymer (fluoropolymer (I')) having a group convertible to an ion exchange group, and when the group convertible to an ion exchange group of the fluoropolymer (I') is converted to an ion exchange group, the ion exchange capacity of the fluoropolymer (fluoropolymer (I)) is 1.1 meq / g resin or more, and the light transmittance is 30 to 60%. The pellets can be used to form ion exchange membranes with excellent electrolysis voltage stability. Although the details of why this is the case are not clear, it is presumed to be due to the following reasons.

[0050] One of the causes of the variation in electrolysis voltage is the non-uniformity of the thickness of the ion exchange membrane. It is considered that such non-uniformity of the thickness of the ion exchange membrane occurs when pellets of a fluoropolymer are used to produce a film-shaped ion exchange membrane, because the pellets stick to each other, causing large pressure fluctuations during film formation. In addition, the sticking of pellets becomes prominent when a fluoropolymer is used as the raw material, which can become a fluoropolymer with high ion exchange capacity when a group that can be converted into an ion exchange group is converted into an ion exchange group. Here, it is presumed that the pellets having a light transmittance within the above range have a roughened surface. Therefore, it is considered that the contact area between the pellets is reduced, and the adhesion between the pellets is suppressed. As a result, the pressure fluctuation during film molding is suppressed, and an ion exchange membrane with excellent uniformity in film thickness is obtained, and it is considered that the variation in electrolysis voltage can be suppressed when the ion exchange membrane is applied to an electrolysis device.

[0051] The light transmittance of the present pellet is 30 to 60%, and from the viewpoint of superior stability of the electrolysis voltage, it is preferably 30 to 50%, and particularly preferably 30 to 40%. The light transmittance of the pellets means the visible light transmittance (measurement wavelength: 400 to 700 nm) measured using a visual transmittance meter (manufactured by Asahi Spectroscopy, MODEL 304 or an equivalent device), and the specific measurement method is as follows.

[0052] First, the luminous transmittance meter is adjusted so that the visible light transmittance is 100% when no sample holder described below is placed on the sample stage of the luminous transmittance meter. Next, a sample holder with a hole of a specified size for fitting a pellet (e.g., a rectangular hole 2 to 3 mm long and 2 to 3 mm wide) is placed on the sample stage, and the light intensity is adjusted so that the visible light transmittance is 25% before the pellet is fitted in the hole of the sample holder. Next, a pellet of the same size as the hole in the sample holder is fitted into the hole in the sample holder, and the visible light transmittance is measured. The visible light transmittance of the pellet is measured at multiple points on one pellet, and the arithmetic average value is calculated. For example, if the pellet is cylindrical, the pellet is fitted into the hole in the sample holder so that light is irradiated onto the side of the pellet, and the pellet is rotated 90 degrees in the circumferential direction, and the visible light transmittance is measured at three points on one pellet, and the arithmetic average value is calculated. Then, the visible light transmittance of the pellet is calculated by converting the visible light transmittance (25%) before the pellet is fitted into the hole in the sample holder to 100% (i.e., the measured visible light transmittance of the pellet is multiplied by 4), and this is the light transmittance (%) of the pellet.

[0053] The fluoropolymer (I') contained in the present pellets is the same as the fluoropolymer (I') used in the present production method described above, and the preferred embodiments such as ion exchange capacity are also the same. The shape, size, surface condition, and uses of the pellets are the same as those of the pellets obtained by the above-mentioned production method. The present pellets are preferably produced by the above-mentioned present production method, since it is easy to adjust the light transmittance within the above range.

[0054] [Ion exchange membrane] The ion exchange membrane of the present invention (hereinafter, also referred to as the present ion exchange membrane) is formed using the present pellet described above. An example of a suitable method for producing the present ion exchange membrane includes a method in which a precursor membrane containing a fluoropolymer having a group that can be converted into the above-mentioned ion exchange group (fluoropolymer (I')) is formed using the present pellets, and then the group that can be converted into an ion exchange group, which is contained in the precursor membrane, is converted into an ion exchange group to obtain the present ion exchange membrane containing a fluoropolymer having an ion exchange group (fluoropolymer (I)).

[0055] [Method for producing precursor film] The precursor membrane can be produced by extrusion. Specifically, the pellets are fed to a known melt extruder for film production, and the melt of the pellets is extruded from a nozzle (e.g., a T-die) of the melt extruder to form a film, thereby obtaining a precursor membrane. The melting temperature of the pellets is preferably 150 to 350°C, and more preferably 200 to 300°C.

[0056] The precursor membrane may have a reinforcing material embedded therein. The reinforcing material can be embedded in the precursor membrane by a known method. For example, when forming a multi-layered ion exchange membrane, a method of sandwiching the reinforcing material between the precursor membranes can be mentioned. The reinforcing material can also be embedded in the precursor membrane by coating both sides of the reinforcing material with a melt of the present pellet.

[0057] Specific examples of the reinforcing material include reinforcing cloth (preferably woven cloth), fibril, and porous body, and among these, reinforcing cloth is preferable. The reinforcing fabric is preferably made of warp yarns and weft yarns, the warp yarns and the weft yarns being orthogonal to each other, and the reinforcing fabric is preferably made of reinforcing yarns and sacrificial yarns. The reinforcing yarn is made of a material that does not dissolve in an alkaline aqueous solution, and is preferably made of at least one type of reinforcing yarn selected from the group consisting of polytetrafluoroethylene, polyphenylene sulfide, nylon, and polypropylene. The sacrificial yarn may be a monofilament consisting of one filament, or a multifilament consisting of two or more filaments. The strength of the ion exchange membrane is maintained by the sacrificial yarn during handling, such as during production of the ion exchange membrane and during installation in an apparatus, but the sacrificial yarn dissolves in the operating environment of the apparatus, thereby reducing the resistance of the ion exchange membrane.

[0058] [Method for producing ion exchange membrane] The present ion exchange membrane containing the fluoropolymer (I) can be obtained by converting groups that can be converted into ion exchange groups of the fluoropolymer (I') contained in the precursor membrane into ion exchange groups. Specific examples of the method for converting groups in the precursor membrane that can be converted to ion-exchange groups into ion-exchange groups include a method of subjecting the precursor membrane to a hydrolysis treatment or an acid-form treatment. Among these, the method of contacting the precursor film with an alkaline aqueous solution is preferred.

[0059] Specific examples of the method for contacting the precursor film with the alkaline aqueous solution include a method of immersing the precursor film in the alkaline aqueous solution and a method of spraying the alkaline aqueous solution onto the surface of the precursor film. The temperature of the alkaline aqueous solution is preferably 30° C. or higher and lower than 100° C. from the viewpoint of productivity of the ion exchange membrane, and the contact time between the precursor membrane and the alkaline aqueous solution is preferably 3 to 300 minutes.

[0060] The alkaline aqueous solution preferably contains an alkali metal hydroxide, a water-soluble organic solvent, and water. Specific examples of the alkali metal hydroxide include sodium hydroxide and potassium hydroxide, and potassium hydroxide is preferred. The alkali metal hydroxide may be used alone or in combination of two or more kinds. In this specification, the water-soluble organic solvent is an organic solvent that is easily dissolved in water, and specifically, the solubility in 1000 ml of water (20°C) is preferably 0.1 g or more, and more preferably 0.5 g or more. The water-soluble organic solvent preferably includes at least one selected from the group consisting of aprotic organic solvents, alcohols, and aminoalcohols, and more preferably includes an aprotic organic solvent. The water-soluble organic solvent may be used alone or in combination of two or more.

[0061] Specific examples of the aprotic organic solvent include dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, and N-ethyl-2-pyrrolidone, with dimethyl sulfoxide being preferred. Specific examples of alcohols include methanol, ethanol, isopropanol, butanol, methoxyethoxyethanol, butoxyethanol, butylcarbitol, hexyloxyethanol, octanol, 1-methoxy-2-propanol, and ethylene glycol. Specific examples of amino alcohols include ethanolamine, N-methylethanolamine, N-ethylethanolamine, 1-amino-2-propanol, 1-amino-3-propanol, 2-aminoethoxyethanol, 2-aminothioethoxyethanol, and 2-amino-2-methyl-1-propanol.

[0062] The content of the alkali metal hydroxide in the alkaline aqueous solution is preferably 1 to 60% by mass. The content of the water-soluble organic solvent in the alkaline aqueous solution is preferably 1 to 60% by mass. When the contents of the alkali metal hydroxide and the water-soluble organic solvent are within the above ranges, the hydrolysis treatment is completed quickly, and the productivity of the present ion exchange membrane is improved. The content of water in the alkaline aqueous solution is preferably 39 to 80% by mass.

[0063] After the precursor membrane is brought into contact with the alkaline aqueous solution, a treatment for removing the alkaline aqueous solution may be carried out. For example, the alkaline aqueous solution may be removed by washing the ion exchange membrane that has been brought into contact with the alkaline aqueous solution with water. After the precursor membrane is brought into contact with the alkaline aqueous solution, the resulting ion exchange membrane may be dried. The drying treatment is preferably a heat treatment, and the heating temperature is preferably 50 to 160° C. The heating time is preferably 0.1 to 24 hours.

[0064] After the groups in the precursor membrane that can be converted to ion exchange groups are converted to ion exchange groups, the ion exchange membrane may be contacted with an aqueous solution containing potassium ions, sodium ions, or hydrogen ions to replace the counter ions (cations) of the ion exchange groups. By replacing the cations of the ion exchange groups with the same cations present in alkaline water, the ion exchange membrane can be subjected to alkaline water electrolysis in an environment in which the replaced cations are present, and the dimensional stability of the ion exchange membrane is improved.

[0065] A hydrophilic layer may be formed on the surface of the precursor membrane or the present ion exchange membrane. The hydrophilic layer may be formed on at least one of the surfaces of the precursor membrane or the present ion exchange membrane. A specific example of the hydrophilic layer is an inorganic particle layer containing inorganic particles. The inorganic particles are preferably excellent in corrosion resistance against acid or alkali and have hydrophilicity. Specifically, at least one selected from the group consisting of oxides, nitrides and carbides of Group 4 elements or Group 14 elements is preferable, at least one selected from the group consisting of SiO2, SiC, ZrO2 and ZrC is more preferable, and ZrO2 is particularly preferable. The hydrophilic layer may contain a binder. As the binder, known binders used in known hydrophilic layers (gas release layers) can be used, such as methyl cellulose and fluorine-containing polymers having sulfonic acid groups. A specific example of a method for forming the hydrophilic layer is a method in which a solution containing inorganic particles and a binder is applied to the precursor membrane or the ion exchange membrane.

[0066] The present ion exchange membrane may be a single layer or a multilayer structure. The multilayer structure ion exchange membrane can be produced, for example, by using a precursor membrane obtained by laminating a plurality of layers made of a fluorine-containing polymer having a group that can be converted into an ion exchange group by a coextrusion method.

[0067] The thickness of the present ion exchange membrane is preferably 30 μm or more, more preferably 40 μm or more, in terms of maintaining a certain strength, and is preferably 500 μm or less, more preferably 300 μm or less, and even more preferably 180 μm or less, in terms of improving current efficiency and voltage efficiency.

[0068] [Fluorine-containing polymer (I)] The fluoropolymer (I) is a fluoropolymer obtained by converting groups that can be converted into ion-exchange groups of the fluoropolymer (I') contained in the precursor membrane into ion-exchange groups. The fluoropolymer (I) is preferably a fluoropolymer having a carboxylic acid type functional group (hereinafter also referred to as fluoropolymer (C)) or a fluoropolymer having a sulfonic acid type functional group (hereinafter also referred to as fluoropolymer (S)) from the viewpoint of better exerting the effects of the present invention. Each of the fluoropolymers will be described in detail below.

[0069] (Fluorine-containing polymer (C)) The fluoropolymer (C) is preferably obtained by converting a group of the above-mentioned fluoropolymer (C') which can be converted into a carboxylic acid type functional group, into a carboxylic acid group. The fluoropolymer (C) preferably contains units based on a fluorine-containing olefin and units based on a monomer having a carboxylic acid type functional group and a fluorine atom. The fluorine-containing olefin may be any of those exemplified above. The fluorine-containing olefin-based unit may be contained in one type alone or in two or more types.

[0070] As the unit based on a monomer having a carboxylic acid functional group and a fluorine atom, a unit represented by the following formula (1C) is preferred. Formula (1C):-[CF2-CF((O) p -(CF2) q -(CF2CFX) r -(O) s -(CF2) t -(CF2CFX') u -COOM C )]- M C is a hydrogen atom, an alkali metal or a quaternary ammonium cation. X, X', p, q, r, s, t and u are the same as in formula (1) above.

[0071] Specific examples of the unit represented by formula (1C) include the following units, and compounds in which p=1, q=0, r=1, s=0-1, t=0-3, and u=0-1 are preferred. -[CF2-CF(O-CF2CF2-COOM C )]-, -[CF2-CF(O-CF2CF2CF2-COOM C )]-, -[CF2-CF(O-CF2CF2CF2CF2-COOM C )]-, -[CF2-CF(O-CF2CF2-O-CF2CF2-COOM C )]-, -[CF2-CF(O-CF2CF2-O-CF2CF2CF2-COOM C )]-, -[CF2-CF(O-CF2CF2-O-CF2CF2CF2CF2-COOM C)]-, -[CF2-CF(O-CF2CF2CF2-O-CF2CF2-COOM C )]-, -[CF2-CF(O-CF2CF(CF3)-O-CF2CF2-COOM C )]-, -[CF2-CF(O-CF2CF(CF3)-O-CF2CF2CF2-COOM C )]-. The unit based on a monomer having a carboxylic acid type functional group and a fluorine atom may be contained alone or in combination of two or more kinds.

[0072] The fluoropolymer (C) may contain units based on other monomers other than the units based on a fluorine-containing olefin and the units based on a monomer having a carboxylic acid type functional group and a fluorine atom. Specific examples of the other monomers include those exemplified above. The content of units based on other monomers is preferably 30 mass % or less based on all units in the fluoropolymer (C) from the viewpoint of maintaining the ion exchange performance.

[0073] (Fluorine-containing polymer (S)) The fluoropolymer (S) is preferably obtained by converting a group of the above-mentioned fluoropolymer (S') which can be converted into a sulfonic acid type functional group into a sulfonic acid group. The fluoropolymer (S) preferably contains units based on a fluorine-containing olefin and units based on a monomer having a sulfonic acid type functional group and a fluorine atom. The fluorine-containing olefin may be any of those exemplified above. The fluorine-containing olefin-based unit may be contained in one type alone or in two or more types.

[0074] As the unit based on a monomer having a sulfonic acid functional group and a fluorine atom, a unit represented by the formula (2S) is preferred. Formula (2S): -[CF2-CF(-L-(SO3M S ) n )]-

[0075] In formula (2S), the definitions of L and n are the same as in formula (2) above. M S is a hydrogen atom, an alkali metal or a quaternary ammonium cation.

[0076] The unit represented by formula (2S) is preferably a unit represented by formula (2S-1), a unit represented by formula (2S-2), or a unit represented by formula (2S-3). Formula (2S-1) -[CF2-CF(-OR f1 -SO3M S )]- Formula (2S-2) -[CF2-CF(-R f1 -SO3M S )]-

[0077] [ka]

[0078] In formulas (2S-1) to (2S-3), R f1 , R f2 The definitions of and r are the same as those in formulas (2-1) to (2-3) above. M S is a hydrogen atom, an alkali metal or a quaternary ammonium cation.

[0079] Specific examples of the unit represented by formula (2S-1) include the following units. In the formula, w is an integer of 1 to 8, and x is an integer of 1 to 5. S The definition is as described above. -[CF2-CF(-O-(CF2) w -SO3M S )]- -[CF2-CF(-O-CF2CF(CF3)-O-(CF2) w -SO3M S )]- -[CF2-CF(-(O-CF2CF(CF3)) x -SO3M S )]-

[0080] Specific examples of the unit represented by formula (2S-2) include the following units. In the formula, w is an integer of 1 to 8. S The definition is as described above. -[CF2-CF(-(CF2) w -SO3M S )]- -[CF2-CF(-CF2-O-(CF2) w -SO3M S )]-

[0081] As the unit represented by formula (2S-3), a unit represented by formula (2S-3-1) is preferable. S The definition is as described above.

[0082] [ka]

[0083] In formula (2S-3-1), R f3 , R f4 The definitions of and r are the same as those in formula (2-3-1) above. S The definition is as described above.

[0084] Specific examples of the unit represented by formula (2S-3) are as follows:

[0085] [ka]

[0086] The unit based on a monomer having a sulfonic acid functional group and a fluorine atom may be contained alone or in combination of two or more kinds.

[0087] The fluoropolymer (S) may contain units based on other monomers other than the units based on a fluorine-containing olefin and the units based on a monomer having a sulfonic acid type functional group and a fluorine atom. Specific examples of the other monomers include those exemplified above. The content of units based on other monomers is preferably 30 mass % or less based on the total units in the fluoropolymer (S) from the viewpoint of maintaining the ion exchange performance.

[0088] [Uses of ion exchange membranes] Specific examples of the use of the present ion exchange membrane include various battery applications such as solid polymer fuel cells, direct methanol fuel cells, redox flow batteries, and air batteries, solid polymer water electrolysis, alkaline water electrolysis, ozone water electrolysis, salt electrolysis, organic electrolysis, and various electrolysis devices such as chlorides or oxides. In addition to the above applications, the membrane can be used as a separator or solid electrode in various types of electrochemical cells for selective cation transport at the binding portion of the cell. In addition to electrochemical applications, the membrane can be used for sensor applications such as various gas sensors, biosensors, light-emitting devices, optical devices, and organic sensors, as well as for solubilizing carbon nanotubes, actuators, and catalyst applications. EXAMPLES

[0089] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to these examples. The blending amount of each component in the tables described below is based on mass.

[0090] [Ion exchange membrane thickness] The cross section of the ion exchange membrane was observed under an optical microscope and the measurement was performed using image analysis software.

[0091] [Ion exchange capacity of fluoropolymer] A fluoropolymer having an ion exchange group was stored for 24 hours in a glove box flushed with dry nitrogen, and the dry mass of the fluoropolymer was measured.Then, the fluoropolymer was immersed in a 2 mol / L aqueous sodium chloride solution at 60°C for 1 hour.The fluoropolymer was washed with ultrapure water, then taken out, and the liquid in which the fluoropolymer had been immersed was titrated with a 0.1 mol / L aqueous sodium hydroxide solution to determine the ion exchange capacity (meq / g resin) of the fluoropolymer.

[0092] [Light transmittance of pellets] First, the luminous transmittance meter (TLV-304-BP, Asahi Spectroscopy) was adjusted so that the visible light transmittance (measurement wavelength: 400 to 700 nm) was 100% when no sample holder, described below, was placed on the sample stage of the luminous transmittance meter. Next, a sample holder (thickness 0.7 mm) with a rectangular hole (hole size: length 2-3 mm × width 2-3 mm) for fitting the pellet was placed on the sample stage, and the light intensity was adjusted so that the visible light transmittance before fitting the pellet into the hole in the sample holder was 25%. Next, a pellet (cylinder-shaped with a diameter of 2-3 mm and a length of 2-3 mm) of approximately the same size as the hole of the sample holder was fitted into the hole of the sample holder so that the side of the pellet was irradiated with light, and the visible light transmittance was measured. The visible light transmittance of the pellet was measured by rotating the pellet 90 degrees in the circumferential direction, measuring the light transmittance at three points for one pellet, and calculating the arithmetic average value. Then, the visible light transmittance of the pellet was calculated by converting the visible light transmittance (25%) before the pellet was fitted into the hole in the sample holder to 100% (i.e., the measured visible light transmittance of the pellet was multiplied by 4), and this was defined as the light transmittance (%) of the pellet.

[0093] [Whether or not there is a bridge in the hopper] When pellets are supplied to the hopper of a melt extruder for film production to produce a film-like ion exchange membrane (precursor membrane), we checked whether or not a state (bridge) occurs in which pellets stick together in the hopper and are not supplied to the screw section (the section where the pellets are melted and kneaded) connected to the hopper. Specifically, a melt extruder (single-axis, screw diameter: 30 mm) was used to produce film (T-die width: 350 mm) for three consecutive hours with the pellet melting temperature set to 260°C, and it was determined whether bridging occurred in the hopper.

[0094] [Film molding pressure fluctuations] Using a melt extruder (single-shaft, screw diameter: 30 mm), the pellet melt temperature was set to 260°C and film (T-die width: 350 mm) was produced continuously for 3 hours. The film molding pressure was measured every 30 minutes from immediately after operation (0 hours) until the end of operation (3 hours), and the film molding pressure fluctuation (%) was calculated according to the following formula. The smaller the fluctuation in molding pressure, the more preferable it is because a film with excellent thickness uniformity can be obtained. The film molding pressure was measured using a resin pressure sensor (Rika Kogyo Co., Ltd.'s "CZ-200P") installed at the tip of the screw. Fluctuation in film forming pressure (%) = [3σ / (arithmetic mean value of film forming pressure measured every hour)] × 100 where σ is the standard deviation of the film forming pressure measured at each time.

[0095] [Electrolysis voltage fluctuation] The ion exchange membrane has an effective current carrying area of ​​1.5 dm 2 The electrolytic cell was placed in a test electrolytic cell (electrolysis surface size: 150 mm length x 100 mm width). In the electrolytic cell, a titanium punched metal (minor diameter 4 mm, major diameter 8 mm) coated with a solid solution of ruthenium oxide, iridium oxide, and titanium oxide was used as the cathode, and a SUS304 punched metal (minor diameter 5 mm, major diameter 10 mm) with ruthenium-containing Raney nickel electrodeposited was used as the cathode. The electrodes were placed so that they were in direct contact with the ion exchange membrane and no gaps were generated. The sodium hydroxide concentration discharged from the cathode chamber was adjusted to 32 mass% and the sodium chloride concentration supplied to the anode chamber was adjusted to 200 g / L. The temperature was 90°C, and the current density was 6 kA / m 2 Under the above conditions, electrolysis of a sodium chloride aqueous solution was carried out, and the electrolysis voltage (V) was measured three days after the start of operation. The electrolysis voltage was measured for 10 ion exchange membranes, and the fluctuation in the electrolysis voltage was calculated according to the following formula. The smaller the fluctuation in the electrolysis voltage, the more excellent the stability of the electrolysis voltage. Fluctuation in electrolysis voltage (%) = [{(maximum electrolysis voltage) - (minimum electrolysis voltage)} / (average electrolysis voltage)] x 100

[0096] [Production of Fluorine-Containing Polymer (S'-1)] CF2=CF2 was copolymerized with a monomer (X1) represented by the following formula (X1) to obtain a fluoropolymer (S'-1) (ion exchange capacity: 1.1 meq / g resin). The blending ratio of each monomer was adjusted so that the ion exchange capacity of the fluoropolymer (S'-1) was the above value. CF2=CF-O-CF2CF(CF3)-O-CF2CF2-SO2F (X1)

[0097] [Production of Fluorine-Containing Polymer (S'-2)] CF2=CF2 was copolymerized with the monomer (X1) represented by the above formula (X1) to obtain a fluoropolymer (S'-2) (ion exchange capacity: 1.25 meq / g resin). The blending ratio of each monomer was adjusted so that the ion exchange capacity of the fluoropolymer (S'-2) was the above value.

[0098] [Production of Fluorine-Containing Polymer (S'-3)] CF2=CF2 was copolymerized with a monomer (X2) represented by the following formula (X2) to obtain a fluoropolymer (S'-3) (ion exchange capacity: 1.90 meq / g resin). The blending ratio of each monomer was adjusted so that the ion exchange capacity of the fluoropolymer (S'-3) was the above value.

[0099] [ka]

[0100] [Production of Fluorine-Containing Polymer (C'-1)] CF2=CF2 was copolymerized with a monomer (Y1) represented by the following formula (Y1) to obtain a fluoropolymer (C'-1) (ion exchange capacity: 1.05 meq / g resin). The blending ratio of each monomer was adjusted so that the ion exchange capacity of the fluoropolymer (C'-1) was the above value. CF2 = CF-O-CF2CF2CF2-COOCH3 (Y1)

[0101] The ion exchange capacity described in the above [Production of fluoropolymer (S'-1)] to [Production of fluoropolymer (S'-3)] and [Production of fluoropolymer (C'-1)] represents the ion exchange capacity of the fluoropolymer having ion exchange groups obtained by treating the fluoropolymers (S'-1) to (S'-3) and (C'-1) by the following procedure. First, the fluoropolymer having groups convertible to ion exchange groups, which has been vacuum heat-treated at 240°C and -0.1 MPaG for 16 hours, is immersed in a solution of dimethyl sulfoxide / potassium hydroxide / water = 30 / 5.5 / 64.5 (mass ratio) at 95°C for 30 minutes to hydrolyze the groups convertible to ion exchange groups in the fluoropolymer and convert them to K-type ion exchange groups, and then washed with water. Then, the polymer is immersed in an aqueous sodium hydroxide solution to convert the terminal groups from K-type to Na-type to obtain a fluoropolymer having ion exchange groups for measuring the ion exchange capacity.

[0102] [Example 1] The fluoropolymer (S'-1) was fed to a melt extruder for pellet production to obtain a melt of the fluoropolymer (S'-1). The obtained melt was extruded through a die heated to 190°C and cooled to obtain a strand (diameter 3.0 mm). The strand was then cut to a length of 3.0 mm to obtain pellets of the fluoropolymer (S'-1). The above-mentioned various measurements were carried out using the obtained pellets. Next, the pellets of the fluoropolymer (S'-1) were fed to a melt extruder for film production, and the pellets were melted at 260°C to obtain a melt of the pellets of the fluoropolymer (S'-1). The resulting melt was extruded through a T-die and formed into a film to obtain a precursor film made of the fluoropolymer (S'-1).

[0103] Next, the precursor membrane was immersed in a solution of dimethyl sulfoxide / potassium hydroxide / water = 30 / 5.5 / 64.5 (mass ratio) at 95 ° C for 30 minutes, and the groups in the precursor membrane that can be converted to sulfonic acid functional groups were hydrolyzed to convert them to K-type sulfonic acid functional groups, and then washed with water. Thereafter, the membrane was immersed in an aqueous sodium hydroxide solution to convert the terminal groups from K-type to Na-type, and then dried to obtain an ion exchange membrane with a membrane thickness of 30 μm. The above-mentioned various measurements were carried out using the obtained ion exchange membrane.

[0104] [Examples 2 to 8, Comparative Examples 1 to 4] Pellets and ion exchange membranes were prepared and various measurements were carried out in the same manner as in Example 1, except that at least one of the type of fluoropolymer for pellet production and the die temperature during pellet production was changed as shown in Table 1. The results of the various measurements are shown in Table 1.

[0105] [Table 1]

[0106] As shown in Table 1, when pellets are produced using a fluoropolymer having a group convertible to an ion exchange group such that the ion exchange capacity when the group convertible to an ion exchange group is converted to an ion exchange group is 1.1 meq / g resin or more, if the die temperature during pellet production is less than 200°C, an ion exchange membrane excellent in stability to the electrolysis voltage can be obtained (see Examples).

[0107] 1 is a photographic image showing the appearance of pellets of the fluoropolymer (S'-1) of Example 1. A photograph of the appearance of the pellets was taken at a magnification of 30 times using a microscope (Keyence Corporation: VHX-900). As shown in Fig. 1, the pellets are generally cylindrical in shape and have grooves formed on the side surface. The direction in which the grooves formed on the side surface extend is the flow direction of the strand during pellet production. The entire contents of the specification, claims, drawings, and abstract of Japanese Patent Application No. 2018-172344, filed on September 14, 2018, are hereby incorporated by reference as the disclosure of the specification of the present invention.

Claims

1. The polymer contains a fluorine-containing polymer having a group that can be converted into an ion-exchange group, the ion exchange capacity of the fluoropolymer when the groups convertible to ion exchange groups of the fluoropolymer are converted to ion exchange groups is 1.1 milliequivalents / gram of dry resin or more; A pellet having a light transmittance of 30 to 60% and having a plurality of grooves formed on the surface.

2. The polymer contains a fluorine-containing polymer having a group that can be converted into an ion-exchange group, the ion exchange capacity of the fluoropolymer when the groups convertible to ion exchange groups of the fluoropolymer are converted to ion exchange groups is 1.1 milliequivalents / gram of dry resin or more; The pellet has a light transmittance of 30 to 60% and a roughened surface.

3. 3. The pellet according to claim 1, wherein the group that can be converted into an ion-exchange group is a group that can be converted into a carboxylic acid type functional group or a group that can be converted into a sulfonic acid type functional group.

4. The pellet according to any one of claims 1 to 3, which is used for producing an ion exchange membrane.

5. A method for producing an ion exchange membrane formed by using the pellet according to any one of claims 1 to 4.

6. The method for producing an ion exchange membrane according to claim 5, wherein the membrane has a thickness of 30 to 180 μm.

7. The method for producing an ion exchange membrane according to claim 5 or 6, which is used for electrolysis of an aqueous alkali chloride solution.

Citation Information

Patent Citations

  • Processing of ion exchange membrane

    JP1983113225A

  • Pellet of polyester and production thereof

    JP1995001447A

  • Ethylene copolymer pellet

    JP2004256740A

  • Cation-exchange membrane, a production method thereof, and an electrolytic cell utilizing same

    WO2010095740A1

  • Method for producing fluorinated ion exchange resin solution

    WO2013115072A1